PENGARUH ASPEK KOMPETENSI KARYAWAN BAGIAN PRODUKSI TERHADAP PENERAPAN KESELAMATAN DAN KESEHATAN KERJA (K3) PADA KONTRAKTOR PT. MULTI HARAPAN UTAMA JOB SITE LOA KULU KUTAI KARTANEGARA - EY. Suharyono, Elisabet Mau, Mardiana, (EKONOMIA, 2020)
This research aims to explain the influence of competency aspects employee which are knowledge, skills and attitudes to the implementation of occupational safety and health on contractors PT. Multi Harapan Utama.In an effort to obtain a secure operational conditions, utilization of workers can be done by providing training related to occupational safety and health (K3), so as to provide knowledge and forms of conduct that true to the occupational safety and health (K3)The analysis tools that used in this research Multiple Linear regression analysis, used to measure the influence of more than one independent variable (knowledge, skills and attitudes) to the dependent variable (occupational safety and health). The function of Linear Regression can be shown as: Y=a + b1x1 + b2x2 + b3x3 + eThe result of the research based on t test results, variable Knowledge has significant influence to the Occupational Safety and Health, variable Skill has significant influence to the Occupational Safety and Health and variable Attitude has significant influence to the Occupational Safety and Health.